ISSN supporting Australian newspaper digitisation - Marjorie Currie; Rebecca Gibbs (Ciência da Informação, 2015)
Abstract In this paper, the authors describe the work being done by the Australian ISSN Agency to support the National Library of Australia’s newspaper digitisation program. The overall process, including the program’s workflows and systems is outlined, as well as the role of the ISSN within the program. Challenges faced by The Agency, particularly ISSN assignment, cataloguing and collaboration are discussed and illustrated with specific case studies. Reflecting on lessons learned provides a valuable mechanism for future directions and the sustainability of providing this service. Keywords: Australian ISSN Agency. National Library of Australia. Newspaper digitisation program.